2014
DOI: 10.1097/pai.0b013e3182a5a02d
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinicopathologic Parameters and Immunohistochemical Features of Triple-negative Invasive Lobular Carcinoma

Abstract: TNLC showed distinct clinicopathologic features such as more frequently seen in the elderly, pleomorphic, larger tumor size, increased expression of vimentin, CK 5, p16, p53, and c-kit. Not all cases showed basal-like phenotype. TNLC is less frequently seen as compared with TNC in invasive ductal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
3
7
1
Order By: Relevance
“…In this study, we characterized 38 primary TN-ILCs (accounting for 0.1% of all breast cancers diagnosed in our institutions within the study period) in comparison with phenotypically close tumors: TN-IDCs and HR + ILCs, matched by stage and grade. In accordance with the results of others, we found that TN-ILCs were more prevalent in elderly patients than TN-IDCs and HR + ILCs [19], and, appeared more unifocal and more often pleomorphic on microscopic examination, with higher nuclear grades than HR + ILCs [17,19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we characterized 38 primary TN-ILCs (accounting for 0.1% of all breast cancers diagnosed in our institutions within the study period) in comparison with phenotypically close tumors: TN-IDCs and HR + ILCs, matched by stage and grade. In accordance with the results of others, we found that TN-ILCs were more prevalent in elderly patients than TN-IDCs and HR + ILCs [19], and, appeared more unifocal and more often pleomorphic on microscopic examination, with higher nuclear grades than HR + ILCs [17,19].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we used a panel of antibodies known as basal markers, including both established (CK5/6 and EGFR) and recently suggested markers (SOX10) [45,46]. We found that only a small subset of TN-ILCs (26.3% versus 93.4% of TN-IDCs) could be classified as BLBCs, which is consistent with previous reports [19]. Our molecular analyses confirmed these results, as most of TN-ILCs were classified as luminal A or HER2-enriched, and not as basal tumors, according to the intrinsic molecular classification.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In whole-body bone scanning, bone metastasis was detected in the T10, T11, L1, L2, L3, and L4 vertebrae. Since the patient was diagnosed with stage IV breast cancer, 6 palliative cycles of 500 mg/m 2 fluorouracil, 50 mg/m 2 doxorubicin, and 500 mg/m 2 cyclophosphamide (FAC) were administered. The patient showed a complete response to the treatment and was followed-up without any medicine for 3 years after the chemotherapy.…”
Section: Case Reportmentioning
confidence: 99%
“…However, although triple-negative lobular carcinomas are rarely encountered in studies related to breast cancer, hormone receptor overexpression is seen at a higher rate. 2 In addition, triple-negative lobular carcinomas is less frequently seen compared with triple-negative carcinomas in invasive ductal carcinoma. 2 In a study, Somali et al found that although invasive lobular histology was less frequent (8.2%), the proportion of medullary, tubular, and mucinous carcinomas was significantly higher (15.9%) in the triple-negative carcinoma group.…”
Section: Introductionmentioning
confidence: 99%